Dominasi Cerai Gugat di Pengadilan Agama Baturaja: Kesadaran Hukum Perempuan dalam Perspektif Hukum Islam - Syabilla Putri Ellfia; Ananda Meva Ayudia; Cindy Marsya Syafitri; Mesa Agung; Aisya Nola; Cindy Wulandari (CV. Doki Course and Training, 2026)
The phenomenon of divorce litigation in Indonesia has experienced a significant increase, dominated by lawsuits filed by wives. This study aims to analyze the factors causing the dominance of divorce litigation in the Baturaja Religious Court, Ogan Komering Ulu Regency, and to examine women's legal awareness from an Islamic legal perspective. The study used a qualitative approach with field research. Data were obtained through interviews, observation, documentation, and literature review. The results show that from January to April 2025, the Baturaja Religious Court handled 275 divorce cases, of which 238 were divorce litigation cases. The main factors driving women to file for divorce include economic problems, domestic violence, infidelity, relationship disharmony, psychological stress, and considerations for the future of children. This study also found that increased education, access to information, and legal aid have contributed to increasing women's legal awareness in fighting for their rights through formal channels. From an Islamic legal perspective, this phenomenon reflects the application of the principles of al-'adl (justice) and al-maslahah (benefit) as an effort to protect the rights of women and children. Thus, the increase in divorce cases not only indicates social change in Indonesian Muslim society, but also the development of women's legal awareness in line with the principles of justice in Islamic law.